2018
DOI: 10.1038/s41598-018-22917-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving the engine power of a catalytic Janus-sphere micromotor by roughening its surface

Abstract: Microspheres with catalytic caps have become a popular model system for studying self-propelled colloids. Existing experimental studies involve predominantly “smooth” particle surfaces. In this study we determine the effect of irregular surface deformations on the propulsive mechanism with a particular focus on speed. The particle surfaces of polymer microspheres were deformed prior to depositing a layer of platinum which resulted in the formation of nanoscopic pillars of catalyst. Self-propulsion was induced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Figures e and f. Although there are some papers that address the effect of mesoporosity and nanoscale roughness on both light‐driven and catalytic micromotors trajectories, the effect of the hierarchical superstructure (above 1 µm) on the micromotor trajectories has been lesser addressed. It was suggested that large pores (in our case, the macropores among the nanosheets) are suitable for water fluid to take place in and alter the motion from linear to off‐linear .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figures e and f. Although there are some papers that address the effect of mesoporosity and nanoscale roughness on both light‐driven and catalytic micromotors trajectories, the effect of the hierarchical superstructure (above 1 µm) on the micromotor trajectories has been lesser addressed. It was suggested that large pores (in our case, the macropores among the nanosheets) are suitable for water fluid to take place in and alter the motion from linear to off‐linear .…”
Section: Resultsmentioning
confidence: 99%
“…After exposure to UV light, the linear correlation switched to parabola for the time intervals shorter than rotational diffusion coefficient, i.e., Δ t ≪ τ R , which suggests that the diffusive motion was changed to directional motion; see Figure g. As time passes τ R (0.68 s), the MSD starts to change from the parabolic to the linear relationship as the propulsion was again randomized . The relatively randomized motion at longer times, i.e., Δ t ≫ τ R is displayed by incomplete circular motion in Figure f (H 2 O 2 ‐free and UV‐on state).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These particles that are asymmetrically coated with a catalytically active metal, exhibit locomotion via bubble generation 63c,68b,69. Longbottom et al developed Janus PS microspheres, partially coated with Pt‐pillars that modified the surface roughness and the catalytic properties . They demonstrated a doubling of speed (15.5 µm s −1 ) when small deformations were present in the surfaces as opposed to the smooth microspheres (7.48 µm s −1 ), but also reduced velocities on highly deformed surfaces (6.41 µm s −1 ) when 10 vol.…”
Section: Fuel‐driven Nano/micromotorsmentioning
confidence: 99%
“…We would, therefore, expect 4 mm spheres to swim with a speed of 0.7 mm s À1 in comparison to 0.5 AE 0.1 mm s À1 which we measured here. The slight reduction in the observed speed could be the result of multiple factors such as the non-perfect particle sphericity, surface roughness, 47 particle material, and Pt coating. [48][49][50]…”
Section: Spherical Particlesmentioning
confidence: 99%